Success through innovation and change – consultancy report on strategy for E.ON UK. - Maciuk, Aneta; Paramashivaiah, Roshan; Seal, Devakalpa (2009)
The purpose of this report is to formulate the future strategy for E.ON UK in the face of fast changing environment. The main objective is to identify the strategically attractive opportunities that could reinforce E.ON strategic position. This paper provides in–depth analysis of internal and external environments of E.ON in order to answer the research question about future strategic choices. Based on the models used and concepts applied we were able to get an overview of the UK Utilities industry and E.ON. The research was mainly focused one the Retail part of the company however Generation, Services and Energy Efficiency businesses were given significant importance. Based on the identified issues and in-depth analysis we were able to provide the company with recommendations. As a main recommendation the Company should take steps to become a leader in Energy Efficiency market (“Best Efficiency Business”/BEB) by combined approach within all the businesses. E.ON should try to increase customer awareness and touch points to facilitate its new strategy. It should also try to convince the regulators about it future proceedings and influence policies that could put E.ON well ahead of the race. E.ON should try to avoid the commodity trap (competing on price) and try to differentiate in terms of service and value creation. When it comes to the mandatory investment in Energy Efficiency E.ON should invest the funds strategically in downstream activities so that it could generate significant revenues out of it. The Energy Efficiency market is open for every Utility company but it depends on how strategically a Utility firm can capture the opportunity and gain advantage by being the first mover through innovations in product and services.